Magnetic studies of SiO2 coated CoFe2O4 nanoparticles - Limaye, M.V. (Journal of Magnetism and Magnetic Materials, 2017)
Oleic acid capped CoFe2O4 nanoparticles which exhibit a high coercivity of ∼9.47 kOe at room temperature were coated with a robust coating of SiO2. We have used chemical synthesis method to obtain SiO2 coated CoFe2O4 nanoparticles with different weight percentages of CoFe2O4 in SiO2 (1.5, 3.1 and 4.8 wt.%). The morphological investigation of the coated nanoparticles by transmission electron microscopy shows that the particles are spherical with average size ∼160 nm. Infrared spectroscopy reveals that oleic acid capping on the surface of CoFe2O4 nanoparticles is retained after silica coating process. The complete coating of SiO2 on CoFe2O4 nanoparticles is confirmed by X-ray photoelectron spectroscopy as there is no signature of cobalt or iron ions on the surface. Magnetic measurements show that coercivity of SiO2 coated CoFe2O4 particles remains more or less unaffected as in CoFe2O4 nanoparticles at room temperature. In addition, the temperature dependent magnetic measurements show that at 5 K the CoFe2O4 and SiO2 coated 1.5 wt.% CoFe2O4 samples exhibit a very high value of coercivity (∼20 kOe) which is more than twice as compared to room temperature coercivity value (∼9.47 kOe). We conclude that silica coating in our study does not significantly affect the coercivity of CoFe2O4 nanoparticles.
Keywords: Coatings; coercive force; High Resolution Transmission Elctron Microscopy; infrared spectroscopy; Magnetic materials

Surface disordered rutile TiO2-graphene quantum dot hybrids: a new multifunctional material with superior photocatalytic and biofilm eradication properties - Biswas, A.; Salunke, G.; Khandelwal, P.; Das, R.; Poddar, P. (New Journal of Chemistry, 2017)
The controlled introduction of defects in semiconductors has contributed to the development of electronic devices and technologies. Recently, chemical control over defects, formation of new hybrid materials and multifunctional nanostructures have been sought in energy, health, and environment related technologies. Surface-disordered anatase-TiO2 has received wide attention due to its exceptional photocatalytic performance. Herein, we demonstrate, for the first time, a one-step aqueous-phase synthesis of a surface-disordered rutile TiO2-graphene quantum dot (TG) hybrid material. The TG-hybrid is a rutile-TiO2 matrix in which homogeneous in situ insertion of GQDs occurs during the growth of the TiO2 particles. The TG-hybrid material showed superior photocatalytic performance with similar to 98% solar light driven photo-degradation of methylene blue (MB) dye within 6 min and similar to 86% of rhodamine-B (RhB) within 4 min which is much better than the photocatalytic performance shown by the rutile-TiO2 (similar to 30% and similar to 20%, respectively) and GQDs (similar to 15% and similar to 8%, respectively), themselves. Moreover, the TG-hybrid also showed enhanced toxicity to Gram-positive (S. aureus) as well as Gram-negative (E. coli, P. aeruginosa) bacterial cells. The growth-curves of E. coli cells, after incubating them with increasing concentrations of the TG-hybrid, showed that the TG-hybrid could effectively inhibit the growth of E. coli cells at a concentration of 60 mu g mL(-1). The effect of UV-light exposure on the bacterial-biofilm disruption by the TG-hybrid material was also investigated. It was observed that in the presence of UV-light, the biofilm disruption done by the TG-hybrid was larger in comparison to the TiO2 and GQDs alone, under the same conditions. The increase in the formation of reactive oxygen species (ROS) in the presence of sunlight for the TG-hybrid may be the reason behind its superior antibacterial and biofilm eradication properties. We believe that the TG-hybrid material will have applications in energy, health and environment related technologies.